HIV-1 Tat-induced disruption of epithelial junctions and epithelial-mesenchymal transition of oral and genital epithelial cells lead to increased invasiveness of neoplastic cells and the spread of herpes simplex virus and cytomegalovirus - Tugizov, Sharof (Frontiers in Immunology, 2025)
Human immunodeficiency virus (HIV-1) transactivator Tat is a unique multi-functional viral protein secreted by infected cells. Although its primary function is to promote HIV-1 transcription, secreted Tat interacts with neighboring cells and induces numerous disease-associated pathological changes. Despite the substantial reduction of viral load and disease burden, Tat expression and secretion persist in people living with HIV who are undergoing treatment with highly effective combination antiretroviral therapy (cART). Tat interacts with both oral and genital epithelial cells and impairs their mucosal barrier functions, which facilitates the entry of other pathogenic viruses. Tat-mediated interactions with both human papillomavirus (HPV) -infected and HPV-negative neoplastic epithelial cells lead to epithelial-mesenchymal transition and increased invasiveness of malignant cells. Likewise, Tat-induced disruption of oral epithelial cell junctions leads to herpes simplex virus-1 (HSV-1) infection and spread via exposure of its receptor, nectin-1. HIV-1 Tat facilitates infection and spread of human cytomegalovirus (HCMV) by activating mitogen-activated protein kinases (MAPK) and promoting NF-κB signaling, both critical for the replication and production of progeny virions. HIV extracellular Tat also plays a critical role in human herpesvirus 8 (HHV8) -caused Kaposi sarcoma (KS) pathogenesis by synergizing with HHV-8 lytic proteins and promoting the proliferation, angiogenesis, and migration of endothelial cells. Collectively, these findings emphasize the critical impact of HIV-1 Tat on HIV/AIDS pathogenesis during the cART era and highlight the need for further research on the molecular mechanisms underlying Tat-mediated interactions with oral and genital mucosal epithelial cells.